2021
DOI: 10.3390/toxins13090638
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Reduction of Fumonisin B1 by the New Isolate Serratia marcescens 329-2

Abstract: The mycotoxin fumonisin (FB) has become a major problem in maize products in southeastern Asia. Fumonisin can affect the health of humans and many animals. Fumonisin contamination can be reduced by detoxifying microbial enzyme. Screening of 95 potent natural sources resulted in 5.3% of samples yielding a total of five bacterial isolates that were a promising solution, reducing approximately 10.0–30.0% of fumonisin B1 (FB1). Serratia marcescens, one of the dominant degrading bacteria, was identified with Gram s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…Results of these studies showed that the hydrolase and transferase enzymes, which can cooperate in the degradation of fumonisin, showed high expression compared to their levels in the control samples. These studies showed that Serratia marcescens 329-2 is a novel bacterium with the potential to reduce FB 1 , and the production of FB 1 -reducing enzymes should be further investigated [67].…”
Section: Novel Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Results of these studies showed that the hydrolase and transferase enzymes, which can cooperate in the degradation of fumonisin, showed high expression compared to their levels in the control samples. These studies showed that Serratia marcescens 329-2 is a novel bacterium with the potential to reduce FB 1 , and the production of FB 1 -reducing enzymes should be further investigated [67].…”
Section: Novel Methodsmentioning
confidence: 99%
“…In terms of mycotoxin reduction, novel approaches have shown that fumonisin contamination can be reduced by detoxifying a microbial enzyme. In study [67], the bacterium Serratia marcescens 329-2 was identified from maize with high activity towards the reduction of FB 1 . A hydrolase and a transferase with increased expression in bacterial cells were also found, which may indicate a potential for the development of FB 1 -reducing enzymes [67].…”
Section: Novel Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to a recent study, the hydrolase and transferase enzymes of Serratia marcescens have shown the FB1 degradation (37%) efficiency. However, microbial methods may decrease the food quality by absorbing nutrients and emitting byproducts into the food matrices, and they are also more costly (18). These latter .…”
Section: Introductionmentioning
confidence: 99%
“…According to a recent study, the hydrolase and transferase enzymes of Serratia marcescens have shown the FB1 degradation (37%) efficiency. However, microbial methods may decrease the food quality by absorbing nutrients and emitting byproducts into the food matrices, and they are also more costly ( 18 ). These latter studies highlight the importance of careful characterization and evaluation of mycotoxin binders for use in specific mycotoxin contamination as well as appropriate in vivo models of target animal species to ensure efficacy and safety.…”
Section: Introductionmentioning
confidence: 99%